A brief virtual reality-based mindfulness intervention can improve olfactory perception while reducing depression and anxiety symptoms in university students - Jingni Ma; Haoke Li; Chuoyan Liang; Siqi Li; Ziliang Liu; Chen Qu (Humanities & Social Sciences Communications, 2025)
Abstract With universities increasingly offering mindfulness-based interventions to enhance students’ mental health conditions and alleviate the strain on overwhelmed psychological services, this study aimed to investigate the potential effectiveness of a brief VR-based mindfulness intervention for university students with depression and anxiety symptoms. Employing a quasi-experimental design, the present study assessed whether the intervention could enhance students’ mindfulness, olfactory perception, and chemosensory while reducing anxiety and depression symptoms. Forty-nine university students (M = 22.06, 10 males) participated in this quasi-experimental study and were tested at three time points: T1 (pre-intervention), T2 (post-intervention), and T3 (follow-up). The intervention immersed participants in virtual environments featuring natural elements and integrated mindfulness practices. The Eligible participants displayed anxiety symptoms while engaged in the study. We also conducted person-to-person interviews and performed a thematic analysis to understand the participants’ insights and feedback regarding the intervention, aiming to inform and improve the design of subsequent interventions. The findings indicated that the intervention showed an immediate and significant impact on reducing anxiety and depression symptoms while improving mindfulness, olfactory perception, chemosensory, and sensory image. Notably, this reduction in depression and anxiety symptoms persisted for one week. Furthermore, the intervention showed the potential to enhance mindfulness and sensory imagery, with these substantial effects also enduring for one week. Qualitative results further supported the findings from the interviews. This study provides preliminary evidence for the effectiveness of brief VR-based mindfulness interventions in alleviating depression and anxiety symptoms among university students.